2018
DOI: 10.1111/cas.13488
|View full text |Cite
|
Sign up to set email alerts
|

Exosomes serve as nanoparticles to suppress tumor growth and angiogenesis in gastric cancer by delivering hepatocyte growth factor siRNA

Abstract: Exosomes derived from cells have been found to mediate signal transduction between cells and to act as efficient carriers to deliver drugs and small RNA. Hepatocyte growth factor (HGF) is known to promote the growth of both cancer cells and vascular cells, and the HGF‐cMET pathway is a potential clinical target. Here, we characterized the inhibitory effect of HGF siRNA on tumor growth and angiogenesis in gastric cancer. In addition, we showed that HGF siRNA packed in exosomes can be transported into cancer cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
86
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 125 publications
(87 citation statements)
references
References 41 publications
1
86
0
Order By: Relevance
“…The secreted EVs display a potent gene knockdown, when internalized in cancer cell, due to the presence of the anti-miR-21 [155]. EVs overexpressing hepatocyte growth factor (HGF) siRNA drastically reduced HGF and vascular endothelial growth factor (VEGF) expression in gastric cancer [172]. EVs delivery of siRNA against RAD51 and RAD52 causes an inhibition of proliferation and a massive reproductive cell death in human breast cancer cells [173].…”
Section: Indirect Loadingmentioning
confidence: 99%
See 1 more Smart Citation
“…The secreted EVs display a potent gene knockdown, when internalized in cancer cell, due to the presence of the anti-miR-21 [155]. EVs overexpressing hepatocyte growth factor (HGF) siRNA drastically reduced HGF and vascular endothelial growth factor (VEGF) expression in gastric cancer [172]. EVs delivery of siRNA against RAD51 and RAD52 causes an inhibition of proliferation and a massive reproductive cell death in human breast cancer cells [173].…”
Section: Indirect Loadingmentioning
confidence: 99%
“…Inhibit schwannoma tumor growth [171] Exosomes from HEK 293T HGF siRNA Inhibition of tumor growth and angiogenesis in gastric cancer [172] Exosomes from breast cancer cells RAD51 and RAD52 siRNA Gene therapy against breast cancer [173] Extracellular vesicles from mesenchymal stem cells TNF-related apoptosis-inducing ligand (TRAIL)…”
Section: Evs Type Nanotechnological Modification Application Referencementioning
confidence: 99%
“…Because of the low stability of siRNA, exosome‐based delivery is favorable. The pathologic function and therapeutic potential of several exosomal miRNA and siRNA in cancer have been evaluated in vitro and in vivo . These therapeutic agents can influence on cellular functions by silencing target genes, such as the cyclin‐dependent kinase 2 (CDK2) implicated in the regulation of cell cycle, the transcription factor E2F2, and the Sp1 transcription factor (SP1) involved in the regulation of cell proliferation, apoptosis, migration and invasion in cancer, and the antiapoptotic protein .…”
Section: Therapeutic Role Of Exosomes In Cancermentioning
confidence: 99%
“…The pathologic function and therapeutic potential of several exosomal miRNA and siRNA in cancer have been evaluated in vitro and in vivo. 24,190,191 These therapeutic agents can influence on cellular functions by silencing target genes, such as the cyclin-dependent kinase 2 (CDK2) implicated in the regulation of cell cycle, the transcription factor E2F2, and the Sp1 transcription factor (SP1) involved in the regulation of cell proliferation, apoptosis, migration and invasion in cancer, and the antiapoptotic protein. 36 For example, apoptosis of the HepG2 hepatocellular carcinoma cell lines by plasma-derived exosomes loaded with antitumor miRNAs (miR-31 and miR-451a) has been successfully promoted.…”
Section: Exosomal Mirnas Circrnas and Lncrnas In Cancer Therapymentioning
confidence: 99%
“…For example, engineered exosomes loaded with doxorubicin can be safely delivered to the tumor microenvironment, demonstrating similar tumor growth inhibition with less adverse effects compared with equipotent free drug (56)(57)(58) (60) demonstrated that exosomes loaded with HGF siRNA could inhibit tumor growth and angiogenesis in gastric cancer. It is hoped that an exosome-based approach for the treatment of gastric cancer with or without peritoneal dissemination will be developed in the near future.…”
Section: Chemoresistance and Exosome-based Treatment Of Peritoneal DImentioning
confidence: 99%